(untitled) (Journal of Informatics Education and Research, 2025)
This study explores the role of Indian ports in the global supply chain through the EPIC (Economic, Political, Infrastructure, Competency) model, addressing the challenges of inefficiencies, high logistics costs, and infrastructure bottlenecks. By examining economic contributions, political and policy impacts, infrastructure development, and competency enhancements, the research provides a comprehensive understanding of how these dimensions influence port performance and global competitiveness. The study adopts a mixed-methods approach, leveraging quantitative analysis of historical data on trade volumes, GDP growth, and vessel turnaround times, alongside qualitative assessments of policy impacts and competency frameworks. Key findings reveal a strong correlation between port throughput and GDP growth, significant efficiency improvements driven by policies like the Sagarmala Project, and infrastructure investments that have enhanced cargo handling capacity. Workforce training initiatives were found to reduce vessel turnaround times, improving overall operational efficiency.The analysis concludes that strategic integration of the EPIC dimensions can transform Indian ports into globally competitive hubs, emphasizing the need for sustained investments, digital transformation, and policy reforms to address existing challenges and enhance supply chain resilience.